The Effect of Problem Based Learning Model on Students' Mathematic Problem Solving Ability on Circle Materials for Class VIII in Cinta Rakyat Private Junior High School, Pematangsiantar - Sipayung, Novita O; Sidabutar, Ropinus (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine the effect of the Problem Based Learning learning model on students' mathematical problem-solving abilities in class VIII circle material at Cinta Rakyat 3 Pematangsiantar Private Junior High School in the Academic Year of 2022/2023. This research is a quantitative study with a quasi-experimental type of research with the research sample being class VIII C as the experimental class and class VIII D as the control class, totaling 60 students. The instrument used in this research is a test in the form of a description. The results of data analysis on pretest questions in the experimental class obtained an average value of 39.77 and in the control, class obtained an average value of 38.13. While the results of the data analysis of the posttest questions in the experimental class obtained an average value of 85.60 and in the control class an average value of 77.83 was obtained. Based on the results of the t-test conducted, it was obtained that tcount > ttable, namely 3.765 > 1.672. So based on the results of the study, it can be concluded that there is an effect of using the Problem Based Learning learning model on students' mathematical problem-solving abilities in class VIII circle material at Cinta Rakyat 3 Private Junior High School Pematangsiantar.